Pengembangan Dokumentasi Intervensi Keperawatan OTEK Berbasis EMR untuk Peningkatan Kinerja Perawat - Wardani, Indrasari; Nihayati, Hanik Endang; Pratiwi, Ika Nur (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to describe to utilize electronic medical records (EMR) for clinical practice, research, education and surveillance. The research method uses systematic review was prepared based on Preferred Reporting Items for Systematic Reviews and Meta-Analyzes (PRISMA). This study used 8 articles that met the inclusion criteria. The results showed that literature search yielded 12,678 articles (337 from Scopus, 3,414 from Science Direct, 8,880 from Proquest and 47 from Pubmed). The research above explains that digitization in hospital nursing holds promise for changing the organization of care processes and, therefore, providing relief for nursing staff shortages. While advanced technology solutions and many application fields, comprehensive implementation remains challenging. Many publications show that electronic medical records (EMR) can make an important contribution to improving service quality. In conclusion, the results of this systematic review provide evidence for policy makers to be able to consider the development of EMR-based OTEK nursing intervention documentation for improving performance. Keywords: Nursing documentation, EMR, Nurse Performance, Nurse working time.